DIGITALIZATION OF INSURANCE COMPANY ACTIVITIES AS AN ELEMENT OF ENSURING ITS FINANCIAL STABILITY (INNOVATIVE ECONOMY, 2024)
Brovko L.I., Savinova Yu.V. DIGITALIZATION OF INSURANCE COMPANY ACTIVITIES AS AN ELEMENT OF ENSURING ITS FINANCIAL STABILITYPurpose. The aim of the article is to study the digitization of the insurance company's activities as an element of ensuring its financial stability in the conditions of political instability and the development of globalization processes.Methodology of research. The methodological basis of the study is the application of a systematic approach in the course of summarizing the indicators of the assessment of the financial stability of insurance companies, a theoretical comparison in the formation of the mechanism of the advantages of digitalization in the research process, a retrospective analysis of dynamic changes to reflect the development trends of the main indicators of insurers' activity in the insurance market.Findings. It is emphasized that the main prerequisites for the digitization of an insurance company as an element of ensuring its financial stability are certain stages of the development of globalization processes in conditions of political instability. It was established that innovative and digital technologies, as well as the level of digital digitization, are among the important factors that have a direct impact on the assessment and improvement of the financial stability of insurance companies. It is argued that the systematized groups of indicators, which are the main basis in the method of calculating coefficients, characterize a certain type of financial stability of the insurance company. The rating of insurance organizations by the size of their own capital, assets and guarantee fund as the main influencing factors on their financial stability in the reporting year was analysed. The modern stages of the development of digitalization in the insurance activity are determined, which contribute to ensuring the competitiveness of the insurance industry and contribute to the improvement of its financial stability.Originality. For the first time, it was established that in the structure of the system for ensuring the financial stability of insurance companies, the approaches to determining important elements, financial indicators and indicators contained in the financial statements of insurers, annual reports, primary accounting information, data on the formation of the client base are fundamental. The process of digitalization of insurance companies was improved, which makes it possible to determine the level of financial stability of insurers with the help of digital technologies.Practical value. It consists in the practical application of innovative digital technologies in the process of digitalization in the insurance market to ensure the financial stability of the activities of insurance organizations.Key words: financial stability, insurance company, insurance activity, digitalization.
Keywords: financial stability; insurance company; insurance activity; digitalization.